2019
DOI: 10.24867/atm-2019-1-003
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural Analysis of Inconel 625 Nickel Alloy / UNS S31803 Duplex Stainless-Steel Dissimilar Weldments

Abstract: In this study, Inconel 625 nickel alloy and UNS 31803 duplex stainless steel (DSS) dissimilar pairs were welded with MIG welding process. Weld metal, obtained with ERNiCrMo-3 filler wire, was subjected to mechanical and microstructural investigations. Notch impact test and micro hardness measurements were realized on weld metal in order to evaluate31803 mechanical properties. Microstructural changes in fusion line of the base metals were examined using optical and electron microscopes. Phase precipitations ric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The failure surface reveals a rapid fracture, probably came from solidification micro-cracks, propagated during the tensile test in 309/INC625 interface. The micrographic exams before the test could not detect these micro discontinuities throughout the interface due to their small dimensions and the internal location, similar to founded by other researchers [31][32][33] . By Figure 12 it is possible to note that the solidification cracks on the buttery were restrict to the 309L-Si weld metal, and were possibly caused by two main factors.…”
Section: Resultssupporting
confidence: 83%
“…The failure surface reveals a rapid fracture, probably came from solidification micro-cracks, propagated during the tensile test in 309/INC625 interface. The micrographic exams before the test could not detect these micro discontinuities throughout the interface due to their small dimensions and the internal location, similar to founded by other researchers [31][32][33] . By Figure 12 it is possible to note that the solidification cracks on the buttery were restrict to the 309L-Si weld metal, and were possibly caused by two main factors.…”
Section: Resultssupporting
confidence: 83%
“…The topologically close pack (TCP) phase was found by the intermetallic compound Ni 3 Cr 2 . This crystalline compound represents a detrimental phase due to its ability to deplete the reinforcing elements in the alloy [25,26]. In the welded specimen of ASTM Mar-M247 alloy by the filler alloy AWS ERNiCrMo-3, the X-ray diffraction inspection revealed the predominant phases, including NiCr and NiCrCoMo, as solid solutions, as illustrated in Figure 11.…”
Section: X-ray Diffraction Inspection Resultsmentioning
confidence: 99%
“…They revealed a change in the microstructure from columnar to cellular structure when the parameters of the welding passes changed. KARAHAN et al [26] studied the weldability and microstructure analysis for welding alloys of stainless steel and Inconel 625 by Metal Inert Gas (MIG). The researchers found that precipitations rich in Mo, and Ti elements lie between the dendritic arms.…”
Section: Introductionmentioning
confidence: 99%